Dealing with Wormhole Attacks in Wireless Sensor Networks Through Discovering Separate Routes Between Nodes - Rezaei, F.; Zahedi, A. (Engineering, Technology & Applied Science Research, 2017)
One of the most common attacks against Wireless Sensor Networks is the wormhole attack. In this attack, the enemy deploys two malicious nodes in two different areas of the network and establishes a high-speed dedicated channel between these two. This will cause the normal nodes in two different areas wrongly think that they are two-hop neighbors. Therefore, this attack will greatly affect the routing algorithms. In this paper, a new distributed algorithm is provided to deal with the wormhole attack. The main idea of the proposed algorithm is to discover separate routes between pairs of two-hop neighboring nodes. The proposed algorithm was implemented and evaluated in terms of true and false detection rate by performing a series of experiments and the results were compared with the base algorithm. The test results showed that the proposed algorithm has desirable efficacy.